Reconsidering Policy Barriers for Justice-Involved College Students - Custer, Bradley D. (2018)
Student affairs professionals are concerned about the access and success of diverse groups of students in U.S. higher education, but systematic barriers continue to confront one understudied population of college students. Justice-involved people–those who have experienced the criminal justice system–face unique challenges on our campuses but are often ignored in discussions of access, retention, and success. To raise awareness about the barriers these student face, this paper offers a descriptive examination of the federal, state, and institutional policies that target justice-involved college students, including policies related to admissions, financial aid, campus housing, student employment, student athletics, and others. Analysis suggests these policies are significant barriers to student success because they prevent students from accessing important services and programs and are harmfully stigmatizing. Recommendations are offered to student affairs professionals on supporting justice-involved college students to overcome the barriers